Aplicaciones de las ondas electromagnéticas en productos alimenticios - Del-Valle, V.; Picouet, Pierre (TECA: Tecnologia i Ciència dels Aliments, 2006)
High frequency waves have a great potential in Food technology, both at house-cooking or industrial use. At home, microwave oven is a widely used equipment at kitchens of developed world. By contrast, in the Food Industry, the use of microwave and radio-frequency techniques is relatively small as a consequence of the need of equipment and specialised staff. The low application of such technology is related to the poor knowledge of the heating process through high frequencies as well as their critical factors that determine the quality of the heating process (dielectric constants, product geometry, distribution in the packaging, etc.). This article intends to clarify the basis of this technology besides describing some applications.